2013
DOI: 10.1002/clen.201300019
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Uranium Ions by Marine Macroalga Padina pavonia

Abstract: The bioremoval potential of brown marine macroalga Padina pavonia for the uranium ions from aqueous solutions was studied under different experimental conditions with respect to the influences of pH, initial uranyl concentration, contact time, biomass dosage, and temperature of solution. Langmuir, Freundlich, Dubinin-Radushkevich, Flory-Huggins, and Brunauer-Emmett-Teller models were applied to describe the biosorption isotherm of uranium ions by P. pavonia biomass. Thermodynamic parameters such as biosorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Extensive studies have been undertaken in recent years with the aim of finding alternative and economically feasible low‐cost sorbents for wastewater treatment. This separation process uses biological materials which are either abundant, such as algae , plant biomass , microbial biomass , or wastes coming from industrial productions and agricultural activities .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been undertaken in recent years with the aim of finding alternative and economically feasible low‐cost sorbents for wastewater treatment. This separation process uses biological materials which are either abundant, such as algae , plant biomass , microbial biomass , or wastes coming from industrial productions and agricultural activities .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results showed that the optimum conditions are pH 4, 75 mg L −1 of initial uranium concentration, 120 min contact time, 10 g L −1 biosorbent dosage, and a temperature of 50°C. Under these conditions, the marine biomass showed an interesting uranium removal efficiency of about 98%, corresponding to a maximum sorption capacity of 162 mg g −1 and a distribution coefficient of 5.26 L g −1 .…”
Section: Adsorption‐based Remediationmentioning
confidence: 99%
“…L.M.Irvine, a red alga. Marine macroalga Padina pavonica (L.) Thivy was successfully used to removing of UO 2 2+ by Aytas et al (Aytas, Gunduz, & Gok, 2014). Bai et al (2014) reported that the uranium could be removed by immobilized cells of Rhodotorula glutinis (Fresen.)…”
Section: Introductionmentioning
confidence: 99%